Proceedings, high altitude revegetation workshop no. 14 - Colorado Water Resources Research Institute, author (Colorado State University. Libraries, 2000)
The 14th high altitude revegetation workshop was held on March 8-10, 2000 at Colorado State University in Fort Collins, Colorado.
August 2000.
Keywords: Revegetation -- United States -- Congresses; Mountain plants -- United States -- Congresses; Tundra plants -- United States -- Congresses; Reclamation of land -- United States -- Congresses